2011
DOI: 10.1371/journal.pone.0019043
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Climate Forcing in Loggerhead Sea Turtle Nesting

Abstract: The long-term variability of marine turtle populations remains poorly understood, limiting science and management. Here we use basin-scale climate indices and regional surface temperatures to estimate loggerhead sea turtle (Caretta caretta) nesting at a variety of spatial and temporal scales. Borrowing from fisheries research, our models investigate how oceanographic processes influence juvenile recruitment and regulate population dynamics. This novel approach finds local populations in the North Pacific and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 45 publications
2
84
3
Order By: Relevance
“…Basin-level differences in environmental and oceanographic conditions can affect population dynamics, access to resources, growth rates and age at maturity [52]. Bailey [18] reinforced this basin-level comparison for leatherbacks (Dermochelys coriacea), suggesting that the processes which drive foraging success may strongly shape the conservation status of conspecific populations.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Basin-level differences in environmental and oceanographic conditions can affect population dynamics, access to resources, growth rates and age at maturity [52]. Bailey [18] reinforced this basin-level comparison for leatherbacks (Dermochelys coriacea), suggesting that the processes which drive foraging success may strongly shape the conservation status of conspecific populations.…”
Section: Discussionmentioning
confidence: 87%
“…The NPSG causes surface convergence and retention of biomass and debris [52]. Various studies have described this feature, often called the 'great North Pacific Garbage Patch' or 'Eastern Garbage Patch' [57].…”
Section: Discussionmentioning
confidence: 99%
“…Wintering storm petrels are thought to move to the Alboran Sea (Soldatini et al 2014), a particularly nutrientrich area that benefits from currents inflowing from the Atlantic Ocean (Agostini & Bakun 2002, Reul et al 2005, Renault et al 2012. This is a first attempt at a deeper analysis of the demography of the Mediterranean storm petrel, considering population growth as a function of oceanographic conditions (Van Houtan & Halley 2011). Some demographic traits of the storm petrel were described in previous studies (Sanz-Aguilar et al 2008, Soldatini et al 2014, but information on senescence and age effects on the species' demography is still lacking.…”
Section: Research Approach and Hypothesesmentioning
confidence: 99%
“…Concern was raised when nesting activity in one of these NWA populations declined markedly from 1998 to 2007 (Witherington et al 2009); however, an increase in nesting numbers has been reported in recent years (Van Houtan and Halley 2011). Anthropogenic threats (Jackson et al 2001, Witherington et al 2009, Finkbeiner et al 2011) and changing oceanographic conditions (Chaloupka et al 2008, Saba et al 2008, Van Houtan and Halley 2011 have been proposed as the main drivers of fluctuations in sea turtle abundance. Because these factors may change depending on geographic location (Kot et al 2010 and references therein), efforts to identify foraging grounds of sea turtles are vital to understand spatial and temporal fluctuations in nesting numbers.…”
Section: Introductionmentioning
confidence: 99%